Identification of small molecule inhibitors targeting FGFR through molecular docking-based screening - Hou, Weibo; Liu, Kun; Wang, Ping; Zheng, Kefan; Kong, Qingran; Wang, Xinyu; Zhao, Qi; Cheng, Liang (Frontiers in Oncology, 2026)
BackgroundFGFRs genetic alterations such as mutations, amplifications, and chromosomal translocations are prevalent in cancers, leading to the initiation and progression of tumors by enhancing FGFR signaling. The substantial problems arising from the lack of decisive clinical evidence have resulted in the cessation of some inhibitor applications, and identifying effective small molecule inhibitors that selectively target FGFRs can advance the therapy of cancers driven by FGFRs abnormalities.MethodsThe three-dimensional structure of the FGFR1/2/3/4 protein and the amino acid positions within the tyrosine kinase domain were downloaded from the PDB database, and small molecule data were extracted from the ZINC15 database. Then, we used molecular docking and dynamics simulations to assess compounds interacting with FGFR proteins, and screening potential small molecules targeting FGFR. Finally, we evaluated its effects by two CRC cell line HCT116 and NCI-H716.ResultsIn the study, by docking with 2.8 million small molecules, we identified three promising FGFR small molecule inhibitors ranked in the top average absolute difference in free energy. By evaluating the binding stability of the docking pose of the three compounds, we found that ZINC000101867325 could form the stable binding interactions with FGFR1/2/3. And, ZINC000101867325 inhibited the activity of FGFR signaling, and resulted in cell apoptosis and decrease in cell proliferation and migration in colorectal cancer cell lines. In addition, ZINC000101867325 is also predicted to target FGFR2 mutations in colorectal cancer patients.ConclusionWe predicted three small molecules targeting FGFRs, and ZINC000101867325 shows superior chemical bond types and stability with FGFR1/2/3, and inhibits FGFR signaling in CRC cell lines. This study provides novel FGFRs inhibitors, which enrich treatment strategies for cancers.